Heterogeneous chemistry in the 3-D state: an original approach to generate bioactive, mechanically-competent bone scaffolds. (23rd November 2018) - Tampieri, Anna; Ruffini, Andrea; Ballardini, Alberto; Montesi, Monica; Panseri, Silvia; Salamanna, Francesca; Fini, Milena; Sprio, Simone
Abstract : Heterogeneous gas–solid reactions drive the biomorphic transformation of natural wood into large 3-D osteoinductive hydroxyapatite scaffolds with damage-tolerant mechanical performance. Abstract : The present work investigates heterogeneous gas–solid reactions involved in the biomorphic transformation of natural wood into large 3-D hydroxyapatite (HA) scaffolds recapitulating physico-chemical, morphological and mechanical features typical of natural bone. In particular, we found that the use of a reactive CO2 /H2 O gas mixture, under supercritical conditions at high pressure, permits to control heterogeneous CaO-CO2 reactions throughout the whole bulk and to direct the nucleation-growth of CaCO3 at a relatively low temperature, thus obtaining a highly reactive 3-D precursor enabling the formation of a large biomorphic HA scaffold preserving fine nanostructure by a hydrothermal process. To the best of our knowledge, the application of heterogeneous chemical reactions in the 3-D state is an original way to generate large HA scaffolds maintaining bio-relevant ionic substitutions, with specific regard to Mg 2+, Sr 2+ and CO3 2− ions, conferring a superior ability to guide cell fate. We hypothesize that the original nanostructure of the final 3-D HA scaffold, not achievable by the classic sintering procedure, and the multi-scale hierarchical organization inherited by the original template, account for its high compression strength with damage-tolerant mechanical behaviour. The ability of the new scaffold to induce bone regeneration is attested by the overexpression of genes, early and late markers of the osteogenic differentiation pathway, and by the in vivo osteoinductivity. We hypothesize that the unique association of bioactive chemical composition, nanostructure and multi-scale hierarchy can synergistically act as instructing signals for cells to generate new bone tissue with organized 3-D architecture. These results point to its great applicative potential for the regeneration of large bone defects, which is a still unmet clinical need.